1998
DOI: 10.1080/00288233.1998.9513317
|View full text |Cite
|
Sign up to set email alerts
|

Use of carcass density for determining carcass composition in beef cattle

Abstract: A study of 38 beef sides (total dissected fat 16.5%-33.0%) showed that densities of forequarter, hindquarter, and side, each predicted percentage carcass components with less accuracy than 12th rib fat thickness. Hot carcass weight added to density of side improved the predictions of fat and bone only slightly (standard errors of estimate of 3.45% and 0.99%, respectively) over density of side alone. Density of primal cuts or combinations of primal cuts predicted carcass composition with lower standard errors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…This is a novelty. On the other hand, contrary to our research, the investigations conducted in [ 19 , 20 , 21 , 22 , 23 ] did not identify different types of meat.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is a novelty. On the other hand, contrary to our research, the investigations conducted in [ 19 , 20 , 21 , 22 , 23 ] did not identify different types of meat.…”
Section: Introductioncontrasting
confidence: 99%
“…It worth noticing that, recently some attempts have been undertaken to explore density measurements to investigate the properties of meat materials [ 19 , 20 , 21 , 22 , 23 ]. However, these works are mainly focused on the investigation of the physicochemical properties and chemical composition of meat materials, not on the discrimination of various types of MSM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, with a reported average cortical thickness of 2.3mm (± 0.13 mm) and Bone Mineral Density of 66 , bovine ribs are frequently employed in most bone simulation experiments used in agricultural as well as general surgical sciences. Finally, considering the grease, muscle and fat content of typical domestic bovine individuals 67 , alongside the general size of P. pardus teeth, it was concluded that the use of rib elements for this sample was the closest possible analogy to the tooth marks collected from other animals.…”
Section: Methodsmentioning
confidence: 96%
“…According to Gardner et al (1997), the evaluation technique used to predict meat yield must be able to function online in a commercial setting without disrupting the normal product flow. Johnson and Chant (1998) noted that research has used very expensive technologies to improve the accuracy of carcass composition prediction, whereas Shackelford et al (1995) reported that, to their knowledge, equations to predict boneless and totally trimmed retail cut yields have not been published.…”
Section: Introductionmentioning
confidence: 99%